2022
DOI: 10.1108/ijaim-05-2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

Do multiple directorships stimulate or inhibit firm value? Evidence from an emerging economy

Abstract: Purpose This study aims to examine the potential influence of multiple directorships (MDs) on the firm value of listed firms in Jordan. Design/methodology/approach Using a sample of 1,067 firm-year observations of Jordanian listed companies from 2010 to 2020, this study applies a pooled ordinary least squares regression model to examine the above-stated relationship. This technique was supported by conducting a generalized method of moments estimation to address the possible occurrence of endogeneity concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…According to Omondi and Muturi (2013), a company's performance is a function of the organization’s ability to obtain and manage its resources in order to develop a competitive advantage (Gallegos Mardones and Ruiz Cuneo, 2020). Corporate performance can be divided into two main categories, namely; accounting-based measures, for example, ROA (Haniffa and Hudaib, 2006; Abdallah and Ismail, 2017; Saidat et al ., 2019: 2020a, b; Marashdeh et al ., 2021) and market-based measures, for example, Tobin's Q (Christensen et al ., 2015; Saidat et al ., 2020a, b; Alhaddad et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…According to Omondi and Muturi (2013), a company's performance is a function of the organization’s ability to obtain and manage its resources in order to develop a competitive advantage (Gallegos Mardones and Ruiz Cuneo, 2020). Corporate performance can be divided into two main categories, namely; accounting-based measures, for example, ROA (Haniffa and Hudaib, 2006; Abdallah and Ismail, 2017; Saidat et al ., 2019: 2020a, b; Marashdeh et al ., 2021) and market-based measures, for example, Tobin's Q (Christensen et al ., 2015; Saidat et al ., 2020a, b; Alhaddad et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the latest research from Ratri et al (2021) proposed that a busy CEO holds positions in multiple organizations and that this situation is related to their effectiveness at work. In general, there are two different arguments about busy CEOs: the quality hypothesis and the busyness hypothesis (Alhaddad et al , 2022). According to the quality hypothesis, a busy CEO may be a CEO with a positive reputation, suggesting high-quality performance in managing the company (Fama, 1980; Fama and Jensen, 1983).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, their ability to monitor and lead the company to the fullest extent possible is limited. Previous studies have proven that busy directors significantly reduce company performance (Alhaddad et al , 2022; Cashman et al , 2012). Furthermore, Bazrafshan and Hesarzadeh (2022) found that busy directors significantly reduce the overall company productivity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations